Leaning into the spirit: ecumenical perspectives on discernment and decision-making in the church - Miller, Virginia; Moxon, David; Pickard, Stephen K. (Palgrave Macmillan, 2019)
Section I. The spirit of ecumenism: theological impulses.Spirit Christology: re-thinking Christo-centric theology /Michael Welker --God's Spirit, the human spirit, and the outpouring of the Spirit /Michael Welker --Theological horizons for an ecumenical future: a response to Michael Welker /The Rt. Rev'd. Prof. Stephen Pickard --Section II. Context for discernment and decision-making.A critical reflection of the role of "context" in discernment, decision-making and reception /Mary-Anne Plaatjies-Van Huffel --Receptive ecumenism in Africa: lessons learned from the actual faith of everyday Christians /Stan Chu Ilo --Ecumenical thrusts for discernment from the perspectives of the Indian subcontinent /Paul Pulikkan --Chiara Lubich and decision-making: a spiritual methodology of mutual reception based on Christ crucified and forsaken /Callan Slipper --Section III. Receiving through dialogue: past and present.The church local, regional and universal: a delicate balance. A recent ecclesiological statement of ARCIC III /Adelbert Denaux --United not absorbed: the Malines conversation revisited /Keith Pecklers --The anniversary of the Reformation as a moment for ecclesial learning /Gerard Kelly --Receptive ecumenism in the context of bilateral dialogues /Raymond K. Williamson --Section IV. The spirit of convergence: a way forward?Reconciling theology: three concepts for convergence /Paul Avis --A ministry of Mary? The question of ordination of women revisited in light of the theology of complementarity /Virginia Miller --Ecumenism for a global church: Can the churches of the West and those of the global South learn from each other? /Thomas Rausch --Discerning the call of the Spirit to theological-ecclesial renewal: notes on being reasonable and responsible in receptive ecumenical learning /Paul D. Murray --Does receptive ecumenism have a future? /Peter Carnley.
Many of the chapters in this book were presented at the Fourth International Conference on Receptive Ecumenism, Canberra, Australia, 2017
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2017 -- Canberra; Weltkirche; Ökumenische Bewegung